Prospective Evaluation of Positivity Rates of Aspergillus-Specific IgG and Quality of Life in HIV-Negative Tuberculosis Patients in Lagos, Nigeria - Oladele, Rita O.; Gbajabimiala, Titi; Irurhe, Nicholas; Skevington, Suzanne M.; Denning, David W. (Frontiers in Cellular and Infection Microbiology, 2022)
Background: Pulmonary tuberculosis (PTB) often results in residual anatomical and functional changes despite therapeutic cure, and may be complicated by chronic pulmonary aspergillosis (CPA). In this study we determined patients’ perceived health-related quality of life (HRQoL) during and after PTB therapy and compare it with their Aspergillus specific IgG levels.. Methodology: We conducted a longitudinal study amongst TB patients attending two DOTS clinic in Lagos, Nigeria. 200 confirmed TB patients were recruited over nine months, with 5 visits at baseline, 3, 6, 9 and 12 months. They were smear/and/or geneXpert/and/or culture positive for TB. HRQoL questionnaires were self-administered. Chest Xray and Aspergillus IgG were collected at each visit. Results: A total of 204 participants were recruited into this study. Most (70.6%) were aged age 18-39 years, only 3.9% were above 60 years; 66.7% of all participants were males. 189 (92.6%) participated in the 3 months assessment, 174 (85.3%) at 6 months, 139 (68.1%) at 9 months, 99 (48.5%) at 12 months. At baseline, only 60.9% felt ‘good’ or ‘very good’ in HRQoL score, which improved to 77% at 6 months. At baseline, 10.4% had positive Aspergillus IgG levels, 15.1% at 3 months, 11.5% at 6 months, 16.7% at 9 months and 19.3% at 12 months. Those with a positive Aspergillus IgG at 6 months had worse physical health (P=0.001), psychological health (P=0.002), social relationships (P=0.006) and environment (P=0.001) domains of HRQoL scores. 38 (18.6%) relocated at end of 6 months treatment, 16 (7.8%) were lost to follow-up and 11 (5.4%) died. Conclusion: Our findings reveal a significant relationship between TB patients QoL and Aspergillus IgG levels. Further follow-up studies and additional imaging are required to determine when patients develop chronic pulmonary aspergillosis and its clinical impact.